ANALYSIS OF CUSTOMER SATISFACTION TO ROOM SERVICE QUALITY ON LITTLE NAN YANG RESTAURANT IN LE GRANDE BALI ULUWATU - I Kade Bagus Dwi Wikrama; I Gusti Agung Mas Krisna Komala Sari; Lien Darlina (Politeknik Negeri Bali, 2018)
The increasing of suporting tourism accomodation in bali, makes competition to get customers more difficult. That caused by the diferent services provided by the each of service provide. One of type of service that often provide to costumers is Room Service, which is room service increasingly increasing caused by customers requestition that basicly want to get and enjoy fast and practicaly without having wait in a long time. Relating of that cased, it makes one of challenge by accomodation provider likes hotel Le Grande Bali Uluwatu to keep compete with others providers. One othe strategy taken by this hotel is to keep the Quality of Service that provide to customers. With optimal service, hope service provider can complete customers expectation, then customers will be back and enjoy the services that given from service provider. The purpose this study is to find out how room service quality by the customers satisfaction at hotel Le Grande Bali Uluwatu and to know which indicators are classified in 4 kuadran diagram kartesius This reserach was conducted in hotel Le Grande Bali Uluwatu with customers who used room service as respondent during stay on hotel Le Grande Bali Uluwatu. Data collected by the questionnaires and analysis by importance performance analisys. The result from the reserach indication that room service in hotel Le Grande Bali Uluwatu provided was quietly satisfactory. It can be seen an the average of the assessement of the implementation of the company reach 4,56%, greater than the rating of impotance which is 4,59%, which mean that quality of service given by hotel Le Grande Bali Uluwatu is quitely satisfactory. In the placement of Cartesian diagram have three indicator that go into quadrant A (main priority) and there are also two indicator that go into the quadrant D (Excessive) so it becomes an important task for the company to pay more attention to the tourists need to complete future customer expectations.